2011
DOI: 10.1016/j.mambio.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic perspective of group-living in a polygynous fruit bat, Cynopterus sphinx

Abstract: a b s t r a c tIn this study, we investigated the genetic social structure of a polygynous fruit bat, Cynopterus sphinx. We tested whether colonies of C. sphinx are substructured and if genetic relatedness among group members is non-random. Although we did not find statistical evidence of genetic structuring of harems within a colony, significant levels of inbreeding within colonies and social associations between related individuals were observed. The average pairwise relatedness was higher for females within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…One clear pattern emerges though, wherein colony males, regardless of the strategies employed, are always more successful than extra-colony males, suggesting that the colony is an important social and mating unit. This is in agreement with Chattopadhyay et al (2011) who reported that harems are not genetically subdivided and might just be social units that do not drive genetic mating systems in this species. Moreover, turnover rates across seasons were lower for males than females (Table S2, supporting information) indicating the importance of colonies for male reproductive success.…”
Section: Harem Size Is Not a Predictor Of Variance In Male Reproductisupporting
confidence: 93%
See 2 more Smart Citations
“…One clear pattern emerges though, wherein colony males, regardless of the strategies employed, are always more successful than extra-colony males, suggesting that the colony is an important social and mating unit. This is in agreement with Chattopadhyay et al (2011) who reported that harems are not genetically subdivided and might just be social units that do not drive genetic mating systems in this species. Moreover, turnover rates across seasons were lower for males than females (Table S2, supporting information) indicating the importance of colonies for male reproductive success.…”
Section: Harem Size Is Not a Predictor Of Variance In Male Reproductisupporting
confidence: 93%
“…Ten microsatellites were used for genetic analyses (Storz 2000). A 10 lL reaction was set for each sample, and PCR conditions followed methods detailed in Chattopadhyay et al (2011). Three microlitre of PCR products was visualized on a 2% agarose gel.…”
Section: Microsatellite Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the genetic divergence between these two tribes (Epomophorini and Myonycterini) was 15% in the studied dataset. The previous study recommended that the species under these tribes share a common ancestor and formed distinct 'Epomophorini-Myonycterini Lineage' (Almeida et al 2011, Chattopadhyay et al 2011. The Epomophorini-Myonycterini lineage maintained 18.2% genetic distance with other Pteropodidae species.…”
Section: Resultsmentioning
confidence: 97%
“…We attempted to provide the best conditions in captivity to minimize disruptions to their natural behaviour. A bamboo basket hanging at the roof of the flight room served as the tent, and a single basket per male because females rarely roost alone in the wild (Chattopadhyay et al, 2011). An automated timer was used to maintain a 12:12 h light-dark cycle.…”
Section: Temporal Grooming Patterns: Observations In Captivitymentioning
confidence: 99%